Analisis Rendahnya Realisasi Bantuan Operasional Kesehatan (BOK) Puskesmas Melalui Mekanisme Salur Langsung Di Kabupaten Bogor Tahun 2023 - Indriansyah, Fahlepi; Soewondo, Prastuti; Permanasari, Vetty Yulianty (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Through the Special Allocation Fund (DAK), effort is made to improve development and community welfare in line with national priorities. Health Operational Assistance (BOK) is the non-physical DAK program in the health sector. This study aims to analyze the causes of the low realization of the 2023 Health Operational Assistance (BOK) Salur budget at the Bogor Regency Health Center using the Public Financial Management (PFM) approach. The study focused on 3 Health Centers in the Bogor Regency area and the Bogor Regency Health Office by considering aspects of distance, time and cost. The research period started from February to April 2025.The results of the study indicate that low budget absorption is caused by several main factors, including a lack of understanding of technical instructions on the implementation limits of the BOK Salur menu, low unit costs set by the local government, and a lack of understanding of the SPJ report organizer by PPTK and the treasurer's financial administrator. This indicates a weakness in the synchronization between the planning, budgeting, and budget implementation stages at the Health Center level. In addition, the limited technical and managerial capacity of the implementers also affects program implementation. Therefore, it is hoped that local governments can further consider the unit cost unit to encourage work performance and motivation. Increasing human resource capacity and strengthening cross-sector coordination to ensure the effectiveness of the use of BOK Salur funds.